37/67‐laminin receptor facilitates neural crest cell migration during enteric nervous system development. Issue 8 (27th June 2020) - Fu, Ming; Barlow‐Anacker, Amanda J.; Kuruvilla, Korah P.; Bowlin, Gary L.; Seidel, Christopher W.; Trainor, Paul A.; Gosain, Ankush
Abstract: Enteric nervous system (ENS) development is governed by interactions between neural crest cells (NCC) and the extracellular matrix (ECM). Hirschsprung disease (HSCR) results from incomplete NCC migration and failure to form an appropriate ENS. Prior studies implicate abnormal ECM in NCC migration failure. We performed a comparative microarray of the embryonic distal hindgut of wild‐type and EdnrB NCC−/− mice that model HSCR and identified laminin‐β1 as upregulated in EdnrB NCC−/− colon. We identified decreased expression of 37/67 kDa laminin receptor (LAMR), which binds laminin‐β1, in human HSCR myenteric plexus and EdnrB NCC−/− NCC. Using a combination of in vitro gut slice cultures and ex vivo organ cultures, we determined the mechanistic role of LAMR in NCC migration. We found that enteric NCC express LAMR, which is downregulated in human and murine HSCR. Binding of LAMR by the laminin‐β1 analog YIGSR promotes NCC migration. Silencing of LAMR abrogated these effects. Finally, applying YIGSR to E13.5 EdnrB NCC−/− colon explants resulted in 80%‐100% colonization of the hindgut. This study adds LAMR to the large list of receptors through which NCC interact with their environment during ENS development. These results should be used to inform ongoing integrative, regenerative medicine approaches to HSCR.